A sala de aula na educação infantil como elemento norteador do processo ensino aprendizagem - SANTOS, Edilena Silva dos (2019)
This work discusses the theme: The Classroom in Early Childhood Education as a Core Element of the Teaching Learning Process, it has the general objective of conducting an analysis about the classroom in Early Childhood Education as a guiding element of the learning process, specific: to investigate the importance of the pedagogical didactic organization of the classroom in Early Childhood Education; and to verify the physical space of the classroom as a stimulating learning environment. For the development of this research we opted for a qualitative methodology with semi-structured interview application with four teachers of the Municipal Child Education Unit Kimie Ohaze located in the municipality of Santarém Novo-PA. As a theoretical basis we brought relevant authors of the area as Kuhmann Jr, Kramer , Horn, Zabalza, Filgueiras and the National Curriculum Guidelines for Early Childhood Education (DCNEIs), among others. The text deals with questions about Early Childhood Education in history, which goes through discussions about DCNEIs, elements that guide the classroom and the organization of this space. The results show that there is an understanding on the part of the educators about the importance of the organization of the living space and that they use and organize the various elements that make up the room, so that the lesson is meaningful for the children. However, it is necessary to research with this same theme in schools with different profiles and the use of different spaces in the schools of Early Childhood Education.